Effects of Terminal Substitution and Iron Coordination on Antiproliferative Activity of l‐Proline‐salicylaldehyde–Thiosemicarbazone Hybrids. Issue 40 (26th October 2017) - Milunović, Miljan N. M.; Dobrova, Aliona; Novitchi, Ghenadie; Gligorijević, Nevenka; Radulović, Siniša; Kožišek, Jozef; Rapta, Peter; Enyedy, Eva A.; Arion, Vladimir B.
Abstract : A series of five iron(III) complexes, namely [Fe(HL 1 )Cl2 ] (1 ), [Fe(HL 2 )Cl2 ]· 1.6H2 O (2· 1.6H2 O), [Fe(HL 3 )(MeOH)Cl2 ]· 0.5H2 O (3· 0.5H2 O), [Fe(HL 4 )(MeOH)Cl2 ]· 0.5H2 O (4· 0.5H2 O) and [Fe(HL 4 )(DMF)Cl2 ]· 0.5Et2 O· H2 O (4′· 0.5Et2 O· H2 O), whereH2 L 1 =l ‐proline‐salicylaldehyde–thiosemicarbazone (l ‐Pro‐STSC), H2 L 2 = pyrrolidine‐substitutedl ‐Pro‐STSC, H2 L 3 = phenyl‐substitutedl ‐Pro‐STSC, andH2 L 4 = naphthyl‐substitutedl ‐Pro‐STSC, have been synthesized. The two ligand precursors (H2 L 3 andH2 L 4 ) and iron complexes were characterized by elemental analysis, spectroscopic methods (UV/Vis, IR, and NMR), ESI mass spectrometry, cyclic voltammetry, and single‐crystal X‐ray crystallography (1–3 and4′ ). Magnetic properties of the five‐coordinate complex2 and six‐coordinate complex4 have also been investigated. The antiproliferative activity of the organic hybrids and their iron(III) complexes have been studied in vitro in five human cell lines and one murine cancer cell line, namely HeLa (cervical cancer), FemX (melanoma), A549 (alveolar basal adenocarcinoma), LS‐174 (colon cancer), MDA‐MB‐453 (breast cancer) and MS1 (transformed murine endothelial), as well as in human noncancerous fetal lung fibroblast cell line (MRC‐5). According to the structure–activity relationship, introduction of aromatic groups such as phenyl or naphthyl enhances the cytotoxic potency of the hybrids in the following orderH2 L 1 <H2 L 2 <H2 L 3 <H2 L 4 . Coordination of the hybrids to iron(III) improves their antiproliferative activity in the majority of investigated cell lines with exception ofH2 L 3 in LS‐174, H2 L 4 in MS1, and bothH2 L 3 andH2 L 4 in FemX cell lines, where an opposite effect was observed. Abstract : N ‐substituted thiosemicarbazone– proline hybrids and their iron(III) complexes were synthesized and characterized. The antiproliferative activity of all hybrids and iron(III) complexes was investigated in five human cancer cell lines and one murine cancer cell line. Introduction of aromatic groups and coordination to iron(III) increase the cytotoxic potential of the proligands.